Kepribadian Tokoh Utama dalam Novel Senja, Hujan, & Cerita Yang Telah Usai Karya Boy Candra (International Forum of Researchers and Lecturers, 2023)
Literary works are human-made products that express the creation’s thoughts, ideas, understanding and feelings about life in imaginative and emotional language. As imaginative works, literary works have an interesting and useful function in unriching the readers inner experience. The aim of this research is to describe the behavior of the main character using the personality structure analysis of sigmund Freud theory which consists of ideas, ego, superego. The type of method used is descriptive qualitative, this method serves to simplify a problem so that i tis easier to break down and understand and easier to descriptive carefully and systematically about the novel Senja, Rain, & Stories That Have Been Finished by Boy Candra. The steps taken in data analysis and data collection are by grouping data according to Freud’s personality structure.